PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIER TERHADAP TURNOVER INTENTION DENGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI VARIABEL MODERASI (Studi Empiris Terhadap Karyawan Pada PT. Berlian Khatulistiwa Line Jakarta) - Bambang Sulistiyo; Tukijan .; endah winarti (DHARMA EKONOMI, 2021)
ABSTRACTThe purpose of this study was to analyze the effect of compensation and career development on turnover intention with transformational leadership as a moderating variable. The population in this study were employees at PT. Berlian Khatulistiwa Line Jakarta, amounting to 142 people. The sample was taken using a purposive judgment sampling method totaling 129 people, but 107 people returned the questionnaire. The data analysis method used in this research is Moderation Regression Analysis. The results of hypothesis testing (H1) show that compensation has a significant negative effect on turnover intention. It is proven that the increased compensation, the lower the turnover intention or the desire of employees to change jobs. The results of hypothesis testing (H2) show that career development has a significant negative effect on turnover intention, the more optimal the career development program is, the lower the employee's turnover intention or desire to change jobs. The results of the interaction test show that the hypothesis (H3) of transformational leadership moderates a significant negative effect of compensation on turnover intention is proven, the more effective the transformational leadership style will strengthen the effect of compensation in reducing turnover intention or the desire of employees to change jobs. The results of the interaction test also show that the hypothesis (H4) of transformational leadership moderates the significant negative effect of career development on turnover intention, the more effective the transformational leadership style will strengthen the effect of career development on reducing turnover intention or the desire of employees to change jobs. Keywords: Compensation, career development, transformational leadership, turnover intention ABSTRAKTujuan dari penelitian ini untuk menganalisis pengaruh kompensasi dan pengembangan karier terhadap turnover intention dengan kepemimpinan transformasional sebagai variable moderasi. Populasi dalam penelitian ini adalah karyawan pada PT. Berlian Khatulistiwa Line Jakarta yang berjumlah 142 orang. Sampel diambil menggunakan metode purposive judgment sampling berjumlah 129 namun yang mengembalikan kuesioner sebanyak 107 orang. Metode analisis data yang digunakan dalam penelitian ini adalah Analisis Regresi Moderasi. Hasil pengujian hipotesis (H1) menunjukkan kompensasi berpengaruh negative signifikan terhadap turnover intention terbukti, semakin meningkat kompensasi maka semakin menurun turnover intention atau keinginan karyawan untuk berpindah kerja. Hasil pengujian hipotesis (H2) menunjukkan pengembangan karier berpengaruh negatif signifikan terhadap turnover intention, semakin optimal program pengembangan karier maka semakin menurun turnover intention atau keinginan karyawan untuk berpindah kerja. Hasil uji interaksi menunjukkan hipotesis (H3) kepemimpinan transformasional memoderasi negatif signifikan pengaruh kompensasi terhadap turnover intention terbukti, semakin efektif gaya kepemimpinan transformasional maka akan memperkuat pengaruh kompensasi menurunkan turnover intention atau keinginan karyawan untuk berpindah kerja. Hasil uji interaksi juga menunjukkan hipotesis (H4) kepemimpinan transformasional memoderasi negatif signifikan pengaruh pengembangan karier terhadap turnover intention, semakin efektif gaya kepemimpinan transformasional maka akan memperkuat pengaruh pengembangan karier menurunkan turnover intention atau keinginan karyawan untuk berpindah kerja. Kata kunci: Kompensasi, pengembangan karier, kepemimpinan transformasional, turnover intention